2016
DOI: 10.1086/688489
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Migration Inhibitory Factor as a Novel Biomarker of Portopulmonary Hypertension

Abstract: Portopulmonary hypertension (POPH) is a poorly understood complication of liver disease associated with significant morbidity and mortality. We sought to identify novel biomarkers of POPH disease presence and severity. We performed a prospective, multicenter, case-control study involving patients with liver disease undergoing right heart catheterization. POPH cases were defined as a mean pulmonary arterial pressure (mPAP) ≥25 mmHg and pulmonary vascular resistance (PVR) >240 dynes˙s˙cm. Plasma samples were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
2
12
0
Order By: Relevance
“…(8) In another study, patients with POPH had higher circulating levels of macrophage migration inhibitory factor, a proinflammatory cytokine. (9) MIF levels were correlated with PVR and were associated with worse survival. Higher levels of endothelin-1, a potent vasoconstrictor and therapeutic target of endothelin receptor antagonists, have also been reported in patients with POPH.…”
Section: Myth: Little Is Known Regarding the Pathophysiology Of Pophmentioning
confidence: 93%
“…(8) In another study, patients with POPH had higher circulating levels of macrophage migration inhibitory factor, a proinflammatory cytokine. (9) MIF levels were correlated with PVR and were associated with worse survival. Higher levels of endothelin-1, a potent vasoconstrictor and therapeutic target of endothelin receptor antagonists, have also been reported in patients with POPH.…”
Section: Myth: Little Is Known Regarding the Pathophysiology Of Pophmentioning
confidence: 93%
“…High levels of MIF were associated with an increased risk of death and MIF production may play a role in disease pathogenesis of PPH [31]. MIF can be an ideal novel biomarker in detecting disease presence and severity [31].…”
Section: Investigationsmentioning
confidence: 98%
“…Hence, it will be useful to develop a sensitive biomarker which can detect disease presence, predict the severity, and treatment response. A recent prospective multicentre case-control study which studied the plasma level of macrophage migration inhibitory factor (MIF) in PPH patients seemed to show promising results [31]. It showed that MIF was higher in both the systemic and pulmonary circulations of patients with PPH compared with controls and correlated with hemodynamic indices of disease severity [31].…”
Section: Investigationsmentioning
confidence: 99%
See 2 more Smart Citations